Chiral features of metal phthalocyanines sitting atop the pre-assembled TiOPc monolayer on Ag(111). Issue 29 (16th July 2019) - Zhu, Hao; Song, Huanjun; Zhao, Wenhui; Peng, Zhantao; Liu, Dan; Xing, Lingbo; Dai, Jingxin; Huang, Zhichao; Liao, Peilin; Wang, Yuan; Wu, Kai
Abstract : Chirality of TiOPc and CuPc caused by their asymmetric intermolecular electronic interactions with the underlying pre-assembled TiOPc molecules. Abstract : The chiral features of the top-layer TiOPc molecules on monolayered TiOPc assembly on Ag(111) were carefully investigated by scanning tunnelling microscopy and local work function measurements. Combined with the density functional theory calculations, systematic experimental explorations of the TiOPc/TiOPc, CuPc/TiOPc and TiOPc/CuPc systems on Ag(111) revealed that the chirality originated from asymmetric electronic interactions rather than conformational change, which might be related to the high performance of the photoelectronic devices based on the MPc complexes.